ANALYSIS OF IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH (K3) ON ROAD CONSTRUCTION WORKERS - Lambang Basri Said Said; Ilham Syafei; Hardiman (Moeslim Indonesian University (UMI), 2020)
Occupational Health and Safety (K3) issues for workers during construction projects often receive less attention from various parties, both from the government or from providers. This lack of awareness of the importance of K3 has resulted in many work accidents in the implementation of construction projects. Accidents that occur in the construction process can hamper the construction process itself so that the objectives of Project Management are not achieved. Research Objectives, To formulate the equation for the application of K3 to road construction workers and to analyze the character, awareness, understanding and compliance of workers with the implementation of K3. The population of workers at the research location is ± 500 people and the number of samples is 100 respondents, the analytical method used is Multiple Linear Regression Software, the results obtained are Character (X1) = 0.282 or 28.2%, Awareness (X2) = 0.226 or 22.6% , Understanding (X3) = 0.258 or 25.8%, Compliance (X4) = 0.242 or 24.2%